Penerapan Terapi Spiritual Dzikir untuk Menurunkan Risiko Perilaku Kekerasan pada Ny. J di Ruang Mawar RSJ Dr. Radjiman Wediodiningrat Lawang - Nabila Ita Nabila; Enggal Hadi Kurniyawan; Fitrio Deviantony; Amalia Kusumaningsih (KHD Production, 2024)
The risk of violent behavior is a condition when an individual will endanger the safety of himself, others, family, community, because of his aggressive behavior. Spiritual dhikr therapy is a therapy that can help reduce signs and symptoms of the risk of violent behavior because when patients listen to reading the Al-Qur’an it can reduce stress hormones, increase feelings of relaxation and divert attention from fear, anxiety and tension. This study aims to apply how to apply spiritual dhikr killing treatment therapy in patients at risk of violent behavior. The method employed is through a case study research design using 5 nursing processes. The patients accept the implementation of nursing strategies to cotrol violent behavior using physical, drug, verbal and spiritual means. Interventions for clients with a risk of violent behavior are adjusted to violent behavior implementation strategies (SP) and then receive additional non-pharmacological therapy in the form of spiritual dhikr therapy at each meeting. Spiritual dhikr therapy is carried out for 10 consscutive days, each meeting consisting of 5 sessions with reading tahlil, tasbih, tahmid, takbir, istighfar. Each session reads the dhikr sentence 33 times wtithin 5 minutes. Before giving dhikr, spiritual therapy there were 9 signs of violent behavior, whereas after giving therapy for 10 days there was a decrease to 2 signs of violent behavior. Spiritual dhikr therapy can reduce signs and symptoms of violent behavior because dhikr can purify the heart and soul, be grateful for what Allah has given, make the body healthy, and prevent oneself from the dangers of lust. Nursing strategies (controlling violent behavior physically, drugs, verbally and spiritually and spiritual dhikr intervention can effectively reduce signs of violent behavior. This can reduce stress hormones, increase feelings of relaxation and distraction of fear, anxiety.